Sobre la función social de la paternidad adoptiva desde la Lex Romana Visigothorum hasta la época del Rey Alfonso X el Sabio = About the social function of adopting parenthood since the Lex Romana Visigothorum until the era of Alfonso X the Wise - Baelo Álvarez, Manuel (Vergentis, 2015)
This paper contributes to the study of the social function of adoptive parenthood (adoptio & adrogatio) in the Lex Romana Visigothorum or Breviario de Alarico (506 d.C) during the reconquest after the islamic invasion in the Municipal Fueros and the code of laws (Fuero of Soria, Fuero Real and Siete Partidas) during the reign of Alfonso X the Wise (1252-1284).